2022
DOI: 10.20396/bjos.v21i00.8665263
|View full text |Cite
|
Sign up to set email alerts
|

Comparative of flexural strength, hardness, and fluoride release of two bioactive restorative materials with RMGI and composite resin

Abstract: Aim: This study was fulfilled to evaluate the flexural strength, micro-hardness, and release of two fluoride ions of bioactive restorative materials (Cention N and Activa Bioactive), a resin modified glass ionomer (Fuji II LC), and a resin composite (Filtek z250). Methods: Forty samples from four restorative materials (Activa Bioactive, Fuji II LC, Cention N, and Filtek Z250) were provided according to the current standards of ISO 4049/2000 guide lines. Subsequently, the samples were stored for 24 hours and 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 34 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…Fluoride ion dynamics provide an advantage for tooth that have a high susceptibility to caries. 7 In the oral cavity, many factors may affect the amount of fluoride ion release in bioactive composite resins, one of which is the pH value of oral cavity and also saliva. In the present study, to represent the condition of oral cavity we conducted for the treatment of bioactive resin in the immersion of lactic acid and artificial saliva.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Fluoride ion dynamics provide an advantage for tooth that have a high susceptibility to caries. 7 In the oral cavity, many factors may affect the amount of fluoride ion release in bioactive composite resins, one of which is the pH value of oral cavity and also saliva. In the present study, to represent the condition of oral cavity we conducted for the treatment of bioactive resin in the immersion of lactic acid and artificial saliva.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of material may attributed to the higher amount of resin matrix leads to increase water absorption and softening the specimen ion release from filler particles can result in separating of the matrix and filler, and also by micro-cracks forming in the interface of filler-matrix interface pH. 7,18 Based on the results of study that has been carried out, the least amount of fluoride ion release was found in the bioactive composite resin immersed in artificial saliva for one day, although the pH value of artificial saliva was lower than that of distilled water. This possibility may occur due to the difference in viscosity between artificial saliva and distilled water.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations